Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1093/ajcn/74.6.808
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum thiamine deficiency in a Karen displaced population

Abstract: Biochemical postpartum thiamine deficiency is still common in Karen refugee women. This situation may be improved by educating lactating women to reduce their consumption of thiaminase-containing foods and by implementing an effective thiamine supplementation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 25 publications
2
90
0
2
Order By: Relevance
“…Il est établi que les épidémies de béribéri touchent plutôt des populations défavorisées ou migratoires [13,15,18,19,25,[28][29][30]35]. Dans notre étude, huit patients sur 11 étaient des migrants, mais cinq sur 11 bénéficiaient d'une couverture sociale traduisant un revenu minimum.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Il est établi que les épidémies de béribéri touchent plutôt des populations défavorisées ou migratoires [13,15,18,19,25,[28][29][30]35]. Dans notre étude, huit patients sur 11 étaient des migrants, mais cinq sur 11 bénéficiaient d'une couverture sociale traduisant un revenu minimum.…”
Section: Discussionunclassified
“…La première forme est due à une carence aiguë en vitamine B1, parfois favorisée par une surconsommation méta-bolique (grossesse, allaitement, apport glucosé exclusif important ou épisode infectieux) [5,13,17,22,30], le plus souvent sur un terrain de carence thiaminique subaiguë.…”
Section: Définitionsunclassified
“…It was suggested that thiamine deficiency in infancy causes long-lasting language impairment. Similarly, in a study of the offspring of Korean mothers suffering with thiamine deficiency, visual alertness was better in infants whose mothers had received thiamine supplements (28) . It is accepted that the thiamine requirements of the mother are increased during pregnancy and lactation, and that in the third trimester of pregnancy the vitamin is preferentially taken up by the fetus (29) .…”
Section: Thiaminementioning
confidence: 92%
“…B-vitamins including thiamine, riboflavin, niacin, pantothenic acid, vitamin B 6 , biotin, and folates are essential nutrients for maternal health during pregnancy and lactation and particularly important for the growth of infant [5][6][7]. Their deficiency can affect pregnancy outcome [5,8], as well as dermal [9,10], blood [8], nervous [11], and digestive system [5,6], even mortality of infant [8,9].…”
Section: Introductionmentioning
confidence: 99%